2021
DOI: 10.3390/cells10112981
|View full text |Cite
|
Sign up to set email alerts
|

Ferroptosis: Cancer Stem Cells Rely on Iron until “to Die for” It

Abstract: Cancer stem cells (CSCs) are a distinct subpopulation of tumor cells with stem cell-like features. Able to initiate and sustain tumor growth and mostly resistant to anti-cancer therapies, they are thought responsible for tumor recurrence and metastasis. Recent accumulated evidence supports that iron metabolism with the recent discovery of ferroptosis constitutes a promising new lead in the field of anti-CSC therapeutic strategies. Indeed, iron uptake, efflux, storage and regulation pathways are all over-engage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
59
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(59 citation statements)
references
References 189 publications
(173 reference statements)
0
59
0
Order By: Relevance
“…Ferroptosis is an iron-ion-dependent form of non-apoptotic cell death leading to oxidative cell death. Surprisingly, CSCs are accumulating iron [ 76 ] and could be specifically targeted with iron-chelating substances such as salinomycin. In this line, it was shown that salinomycin could induce iron load in lysosomes followed by iron-mediated production of reactive oxygen species leading to cell death [ 77 ].…”
Section: The Transcription Factor Nf-κb As a Target In Cancer Stem Cellsmentioning
confidence: 99%
“…Ferroptosis is an iron-ion-dependent form of non-apoptotic cell death leading to oxidative cell death. Surprisingly, CSCs are accumulating iron [ 76 ] and could be specifically targeted with iron-chelating substances such as salinomycin. In this line, it was shown that salinomycin could induce iron load in lysosomes followed by iron-mediated production of reactive oxygen species leading to cell death [ 77 ].…”
Section: The Transcription Factor Nf-κb As a Target In Cancer Stem Cellsmentioning
confidence: 99%
“…The downside is that the iron dependency at the same time makes cancer cells more vulnerable to ferroptosis, which therefore might be considered as a druggable “Achilles heel”. Several ferroptosis inducers have been so far identified and approved with the expectation to bypass the disadvantages of traditional chemotherapies based on induction of apoptosis ( 44 , 45 ). Numerous studies have shown that ferroptosis has consistent antitumor effects or, alternatively, enhances chemosensitivity in OVCA ( 21 ).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, recent discoveries indicated that cancer stem cells (CSCs) might be sensitive to ferroptosis due to their relatively strong dependency on the lipid intake pathways and higher intracellular iron levels compared with regular cancer cells ( 132 , 133 ). Therefore, interference with GPX4 pathways seems to sensitize CSCs to ferroptosis ( 134 136 ). Furthermore, cytotoxic CD8 + T cells could enhance tumor cell lipid peroxidation caused by ferroptosis, thus achieving higher efficacy of PD1 checkpoint blockade therapy ( 137 ).…”
Section: Ferroptosismentioning
confidence: 99%